2007
DOI: 10.1080/08923970701675069
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of T Lymphocyte Proliferation to Antigenic and Mitogenic Stimuli by Benzo(α)pyrene and 2-Aminofluorene Metabolites

Abstract: Here, we attempt to reveal how 2-aminofluorene (AF), benzo(alpha)pyrene (BP) and their major metabolites affect T-cell responses to antigenic and mitogenic stimuli. P-450-related metabolism of these parent compounds to metabolites seems to precede the observed immunosuppression; therefore, we investigated the influence of alpha-naphthoflavone (P-450 inhibitor) and beta-naphthoflavone (P-450 inducer) on BP and AF immunosuppression. We used proliferative responses to concanavalin A and the allogeneic mixed lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Although these limitations preclude the use of epidemiological studies in this analysis to obtain a better mechanistic understanding of the immunotoxicity of BaP, they do provide evidence that the immunotoxic effects observed in animals might also occur in humans. 36 Galvan et al 37,38 Allan et al 39 Blanton et al 40 De Jong et al 41 Holladay and Smith 42 Belitskaya-Levy et al 43 Carfi et al 44 Fang and Zhang 45 N'Jai et al 46 Carfi et al 44 Fujimaki et al 47 Halappanavar et al 48 Schellenberger et al 49 Davila et al 50 Hardin et al 51 Labib et al 52 Wojdani and Alfred 53 Dreij et al 54 Hwang et al 55 Kroese et al 56 Wojdani et al 57 Gao et al 58 Kawabata and White 59 Nebert et al 60,61 Developmental Krieger et al 62,63 Lee and Urso 64 Robinson et al 65 Lummus and Henningsen 66 Laupeze et al 67 Legraverend et al 68 Sagredo et al 69 Rodriguez et al 70 Lecureur et al 71 Lyte and Bick 72,73 Silkworth et al 74 Urso 75 Monteiro et al 76 Lyte et al 77 Shi et al 78 Urso and Johnson 79 Mounho et al 80<...>…”
Section: Plausibility Of Pah Immune Suppression In Humansmentioning
confidence: 99%
“…Although these limitations preclude the use of epidemiological studies in this analysis to obtain a better mechanistic understanding of the immunotoxicity of BaP, they do provide evidence that the immunotoxic effects observed in animals might also occur in humans. 36 Galvan et al 37,38 Allan et al 39 Blanton et al 40 De Jong et al 41 Holladay and Smith 42 Belitskaya-Levy et al 43 Carfi et al 44 Fang and Zhang 45 N'Jai et al 46 Carfi et al 44 Fujimaki et al 47 Halappanavar et al 48 Schellenberger et al 49 Davila et al 50 Hardin et al 51 Labib et al 52 Wojdani and Alfred 53 Dreij et al 54 Hwang et al 55 Kroese et al 56 Wojdani et al 57 Gao et al 58 Kawabata and White 59 Nebert et al 60,61 Developmental Krieger et al 62,63 Lee and Urso 64 Robinson et al 65 Lummus and Henningsen 66 Laupeze et al 67 Legraverend et al 68 Sagredo et al 69 Rodriguez et al 70 Lecureur et al 71 Lyte and Bick 72,73 Silkworth et al 74 Urso 75 Monteiro et al 76 Lyte et al 77 Shi et al 78 Urso and Johnson 79 Mounho et al 80<...>…”
Section: Plausibility Of Pah Immune Suppression In Humansmentioning
confidence: 99%
“…However, a minor fraction of B[a]P is converted to B[a]P‐7,8‐dihydrodiol‐9, 10‐epoxide, which is highly reactive and carcinogenic. This metabolic pathway is mediated by the cytochrome P450 enzyme CYPIA1, also known as aryl hydrocarbon hydroxylase . Apart from its carcinogenic role, B[a]P is also known for its immunotoxicity …”
Section: Discussionmentioning
confidence: 99%
“…The metabolic progression of B(α)P toward carcinogenicity is a function of the BPDE-DNA complex (Luch 2005), and it seemed plausible that this complex is responsible for immunosuppression. However, we found that most of the intermediate metabolites of B(α)P are immunosuppressive (Lee and Urso 2007) and that BPDE-DNA is only partly involved in and not completely responsible for immunosuppression (MoolenaarWirsiy et al 2007). Thus, we hypothesize that thirdparty entities play a decisive role in contributing to immunosuppression.…”
Section: Introductionmentioning
confidence: 94%
“…The most studied PAH, as well as perhaps the strongest carcinogen, is benzo(α)pyrene [B(α)P], a ubiquitous environmental pollutant that is found in such sources as commercial (automobile exhausts; Grimmer and Pott 1983); domestic (cigarette smoke ;Hecht 1999;Phillips 2002), and industry (foundry workers; Santella et al 1993). When this carcinogen enters into a mammalian organism, it is metabolized by the P450 enzyme system to several carcinogenic metabolic intermediates that are immunosuppressive (Lee and Urso 2007). The metabolic progression of B(α)P toward carcinogenicity is a function of the BPDE-DNA complex (Luch 2005), and it seemed plausible that this complex is responsible for immunosuppression.…”
Section: Introductionmentioning
confidence: 98%